Method for producing silicon-containing oxide-coated aluminum nitride particles
By evaporation using a specific organic silicon compound on the surface of the aluminum nitride particles and heating to form a film, the problems of aggregation of aluminum nitride particles and the reduction of moisture resistance are solved, and oxide-coated aluminum nitride particles containing silicon with high thermal conductivity and excellent moisture resistance are achieved.
Patent Information
- Application Number
- CN202380013073.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-16
- Filing Date
- 2023-06-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-06-29
AI Technical Summary
In the prior art, silicon-containing oxide-coated aluminum nitride particles tend to agglomerate, resulting in a decrease in fillability, and the cover film peels off after crushing during the composition during preparation, thereby reducing moisture resistance.
By evaporation using a specific organosilicon compound on the surface of aluminum nitride particles and heating at a temperature above 300°C and less than 1000°C, an oxide film containing silicon is formed, which inhibits aggregation and improves moisture resistance.
The high thermal conductivity and excellent moisture resistance of aluminum nitride particles are maintained, aggregation is suppressed, and fillability is improved, so that the obtained silicon-containing oxide-coated aluminum nitride particles are suitable for heat dissipation materials of electronic components.
Smart Images

Figure BDA0004687918800000021 
Figure BDA0004687918800000031 
Figure BDA0004687918800000032
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing silicon-containing oxide-coated aluminum nitride particles. Background Art
[0002] Aluminum nitride has high thermal conductivity and excellent electrical insulation. Therefore, aluminum nitride is promising as a filler for resin compositions used in products such as heat sinks and sealing materials for electronic components. However, aluminum nitride undergoes hydrolysis by reacting with water and is modified into aluminum hydroxide with low thermal conductivity. In addition, aluminum nitride also produces corrosive ammonia during hydrolysis.
[0003] The hydrolysis of aluminum nitride is also carried out by moisture in the atmosphere. Therefore, products to which aluminum nitride is added may not only suffer from reduced moisture resistance and thermal conductivity under high temperature and high humidity conditions, but may also suffer from corrosion and other performance degradations due to ammonia generated by the hydrolysis of aluminum nitride.
[0004] As a technology for improving the moisture resistance of aluminum nitride, for example, a method for producing silicon-containing oxide-coated aluminum nitride particles has been proposed, wherein the silicon-containing oxide-coated aluminum nitride particles include aluminum nitride particles and a silicon-containing oxide film covering the surface of the aluminum nitride particles, and the production method includes the following steps: a first step of covering the surface of the aluminum nitride particles with an organic silicon compound having a specific structure; and a second step of heating the aluminum nitride particles covered with the organic silicon compound at a specific temperature (for example, refer to Patent Documents 1 and 2).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2020 / 040309
[0008] Patent Document 2: Japanese Patent Application Publication No. 2021-075435 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In the production methods described in Patent Documents 1 and 2, the obtained silicon-containing oxide-coated aluminum nitride particles may aggregate, and if the silicon-containing oxide-coated aluminum nitride particles aggregate, there is a problem that the filling property into various materials is reduced. In addition, if the aggregated silicon-containing oxide-coated aluminum nitride particles are crushed during the preparation of the composition, the silicon-containing oxide film covering the surface of the aluminum nitride particles will peel off, and there is a problem that the moisture resistance of the composition is reduced.
[0011] The present invention has been proposed in view of such actual conditions, and an object thereof is to provide a method for producing silicon-containing oxide-coated aluminum nitride particles which can maintain high thermal conductivity of aluminum nitride particles, have excellent moisture resistance, and have suppressed aggregation.
[0012] Means for solving problems
[0013] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by coating aluminum nitride particles with a specific organic silicon compound by a specific method, thereby completing the present invention. That is, the present invention has the following configuration.
[0014] [1] A method for producing silicon-containing oxide-coated aluminum nitride particles, the silicon-containing oxide-coated aluminum nitride particles comprising aluminum nitride particles and a silicon-containing oxide film covering the surface of the aluminum nitride particles, the method comprising the following steps:
[0015] A first step of vapor-depositing an organosilicon compound having a structure represented by the following formula (1) on the surface of the aluminum nitride particles to obtain the aluminum nitride particles covered with the organosilicon compound; and
[0016] A second step of heating the aluminum nitride particles covered with the organic silicon compound at a temperature of 300° C. or more and less than 1000° C.,
[0017] The first step is carried out in a nitrogen atmosphere, and the partial pressure of the organosilicon compound in the nitrogen atmosphere is 2.6×10 2 ~3.9×10 3 Pa.
[0018]
[0019] (In formula (1), R is an alkyl group having 1 to 4 carbon atoms.)
[0020] [2] According to the method for producing silicon-containing oxide-coated aluminum nitride particles described in the above [1], the rate of change of the particle size distribution width (P2) of the above-mentioned silicon-containing oxide-coated aluminum nitride particles calculated by the following formula (I) relative to the particle size distribution width (P1) of the above-mentioned aluminum nitride particles is less than 10%.
[0021]
[0022]
[0023]
[0024] (In the formula, D90 in P1 and P2 is the particle size at which the cumulative volume is 90%, D50 is the particle size at which the cumulative volume is 50%, and D10 is the particle size at which the cumulative volume is 10%.)
[0025] [3] The method for producing silicon-containing oxide-coated aluminum nitride particles according to [1] or [2] above, wherein the first step is performed by a vapor phase adsorption method.
[0026] [4] According to the method for producing silicon-containing oxide-coated aluminum nitride particles described in any one of [1] to [3] above, the organic silicon compound containing the structure represented by the above formula (1) contains at least one of the compound represented by the following formula (2) and the compound represented by the following formula (3).
[0027]
[0028] (In formula (2), R1 and R2 are each independently a hydrogen atom or a methyl group, at least one of R1 and R2 is a hydrogen atom, and m is an integer of 0 to 10.)
[0029]
[0030] (In formula (3), n is an integer from 3 to 6.)
[0031] [5] The method for producing silicon-containing oxide-coated aluminum nitride particles according to any one of [1] to [4] above, wherein the first step is performed at a temperature of 30 to 200°C.
[0032] Effects of the Invention
[0033] According to the present invention, there is provided a method for producing silicon-containing oxide-coated aluminum nitride particles capable of producing silicon-containing oxide-coated aluminum nitride particles having excellent moisture resistance while maintaining high thermal conductivity of aluminum nitride particles and having suppressed aggregation. DETAILED DESCRIPTION
[0034] Hereinafter, the present invention will be described in detail.
[0035] The present invention also includes any embodiment obtained by arbitrarily selecting or arbitrarily combining the matters described in this specification.
[0036] In the present specification, provisions defined as preferred can be arbitrarily selected, and a combination of provisions defined as preferred can be said to be more preferred.
[0037] In this specification, the description of "XX to YY" means "XX or more and YY or less".
[0038] In this specification, regarding the preferred numerical range (for example, the range of content, etc.), the lower limit and upper limit values recorded in stages can be independently combined. For example, according to the description of "preferably 10 to 90, more preferably 30 to 60", the "preferable lower limit (10)" and the "more preferably upper limit (60)" can also be combined to "10 to 60".
[0039] In this specification, the so-called "cumulative volume 90% particle diameter (D90)" indicates the particle diameter when the cumulative value of volume accumulation in a certain particle size distribution becomes 90%, the so-called "cumulative volume 50% particle diameter (D50)" indicates the particle diameter when the cumulative value of volume accumulation in a certain particle size distribution becomes 50%, and the so-called "cumulative volume 10% particle diameter (D10)" indicates the particle diameter when the cumulative value of volume accumulation in a certain particle size distribution becomes 10%. D90, D50, and D10 are all obtained from the particle size distribution obtained by the laser diffraction scattering method. Specifically, it can be measured by using a laser diffraction / scattering particle size distribution measuring device (made by Microtrac Bell Co., Ltd., "Microtrac MT3300EX2").
[0040] <Method for producing silicon-containing oxide-coated aluminum nitride particles>
[0041] The method for producing silicon-containing oxide-coated aluminum nitride particles of the present invention produces silicon-containing oxide-coated aluminum nitride particles having aluminum nitride particles and a silicon-containing oxide film covering the surface of the aluminum nitride particles. The "silicon-containing oxide" of the silicon-containing oxide film and the silicon-containing oxide-coated aluminum nitride particles will be described in detail later, and examples thereof include silicon dioxide and a composite oxide of silicon and aluminum. Examples of the oxide include oxides, oxynitrides, oxycarbonitrides, and the like.
[0042] Furthermore, the method for producing aluminum nitride particles coated with silicon-containing oxides of the present invention is characterized in that it comprises the following steps: a first step of vapor-depositing an organosilicon compound having a structure represented by the following formula (1) on the surface of aluminum nitride particles to obtain the aluminum nitride particles coated with the organosilicon compound; and a second step of heating the aluminum nitride particles coated with the organosilicon compound at a temperature of 300° C. or higher and less than 1000° C., wherein the first step is carried out in a nitrogen atmosphere, and the partial pressure of the organosilicon compound in the nitrogen atmosphere is 2.6×10 2 ~3.9×10 3 Pa.
[0043]
[0044] (In formula (1), R is an alkyl group having 1 to 4 carbon atoms.)
[0045] [1st step]
[0046] In this step, an organosilicon compound having a structure represented by the above formula (1) is vapor-deposited on the surface of the aluminum nitride particles to obtain the aluminum nitride particles covered with the organosilicon compound.
[0047] <Aluminum nitride particles>
[0048] In the method for producing silicon-containing oxide-coated aluminum nitride particles of the present invention, the aluminum nitride particles used as a raw material can use known materials such as commercial products. The method for producing aluminum nitride particles is not particularly limited, and there are, for example, a direct nitridation method in which metal aluminum powder is directly reacted with nitrogen or ammonia, a reduction nitridation method in which a nitridation reaction is carried out while heating aluminum oxide under a nitrogen or ammonia atmosphere while carbon reduction, and the like.
[0049] As the aluminum nitride particles, particles obtained by sintering an aggregate of aluminum nitride particles into a granular form can be used. For example, sintered particles using high-purity aluminum nitride particles as a raw material can be preferably used.
[0050] Here, the so-called high-purity aluminum nitride particles are particles having a low oxygen content and a small amount of metal impurities. Specifically, for example, high-purity aluminum nitride particles having an oxygen content of 1% by mass or less and a total content of metal impurities (i.e., metal atoms other than aluminum) of 1000 ppm by mass or less are suitable for obtaining higher thermal conductivity of aluminum nitride particles included in silicon-containing oxide-coated aluminum nitride particles.
[0051] The aluminum nitride particles may be used alone or in combination.
[0052] The oxygen content can be measured using an inorganic analyzer equipped with an infrared detector for oxygen detection, etc. Specifically, the oxygen content can be measured using an oxygen / nitrogen / hydrogen analyzer (manufactured by LECO Japan Corporation, “ONH836”).
[0053] The total content of metal atoms other than aluminum can be measured using an ICP (Inductively Coupled Plasma) mass spectrometer, etc. Specifically, the total content of metal atoms other than aluminum can be measured using an ICP mass spectrometer (manufactured by Shimadzu Corporation, “ICPMS-2030”).
[0054] The shape of the aluminum nitride particles used in the present invention is not particularly limited, and examples thereof include amorphous (crushed), spherical, elliptical, plate-like (scaly), etc. Furthermore, when silicon-containing oxide-coated aluminum nitride particles are dispersed in the resin composition as a filler, only aluminum nitride particles of the same type (single substance) having the same shape and structure may be used as the aluminum nitride particles, or a mixture of two or more different types of aluminum nitride particles having different shapes and structures mixed in various ratios may be used.
[0055] When silicon-containing oxide-coated aluminum nitride particles are dispersed in a resin composition, the greater the volume ratio (filling amount) of the aluminum nitride particles constituting the silicon-containing oxide-coated aluminum nitride particles relative to the resin composition, the higher the thermal conductivity of the resin composition. Therefore, the shape of the aluminum nitride particles is preferably close to a spherical shape in which the viscosity of the resin composition caused by the addition of silicon-containing oxide-coated aluminum nitride particles is less increased.
[0056] The cumulative volume 50% particle size (D50) of the aluminum nitride particles used in the present invention is not particularly limited, but is preferably 0.5 μm or more, more preferably 0.5 μm or more and 200.0 μm or less, further preferably 0.8 μm or more and 100.0 μm or less, and particularly preferably 1.0 μm or more and 80.0 μm or less.
[0057] If the D50 of the aluminum nitride particles is within the above range, even when a resin composition comprising aluminum nitride particles coated with an oxide containing silicon is used as a heat dissipation material for power system electronic components, a heat dissipation material with a minimum thickness can be provided, and the coating can easily and uniformly cover the surface of the aluminum nitride particles, thereby further improving the moisture resistance of the aluminum nitride particles.
[0058] <Organic silicon compounds used for coating>
[0059] In the method for producing silicon-containing oxide-coated aluminum nitride particles of the present invention, the organosilicon compound used as a raw material for the silicon-containing oxide film constituting the silicon-containing oxide-coated aluminum nitride particles can be used without particular limitation as long as it is an organosilicon compound containing the structure represented by the above formula (1), regardless of whether it is in a linear, cyclic or branched form. The structure represented by formula (1) is a hydrogen siloxane unit in which hydrogen is directly bonded to a silicon atom.
[0060] In the above formula (1), R, which is an alkyl group having 1 to 4 carbon atoms, is preferably a methyl group, an ethyl group, a propyl group, a tert-butyl group, etc., from the viewpoint of volatilizing the organosilicon compound, and a methyl group is particularly preferred. In the method for producing silicon-containing oxide-coated aluminum nitride particles of the present invention, the organosilicon compound used as a raw material is, for example, an oligomer or a polymer having a structure represented by formula (1).
[0061] As the organosilicon compound, for example, at least one of a compound represented by the following formula (2) and a compound represented by the following formula (3) is suitable.
[0062]
[0063] (In formula (2), R1 and R2 are each independently a hydrogen atom or a methyl group, at least one of R1 and R2 is a hydrogen atom, and m is an integer of 0 to 10.)
[0064]
[0065] (In formula (3), n is an integer from 3 to 6.)
[0066] In particular, the cyclic hydrogen siloxane oligomer in which n is 4 in the above formula (3) is excellent in forming a uniform film on the surface of aluminum nitride particles. The weight average molecular weight of the organosilicon compound having the structure shown in formula (1) is preferably greater than 100 and less than 2000, more preferably greater than 150 and less than 1000, and further preferably greater than 180 and less than 500. It is speculated that by using an organosilicon compound having a weight average molecular weight in this range and having the structure shown in formula (1), a thin and uniform film can be easily formed on the surface of aluminum nitride particles. It should be noted that in formula (2), m is preferably 1.
[0067] In this specification, the weight average molecular weight is a polystyrene-equivalent weight average molecular weight using gel permeation chromatography (GPC), and specifically, it can be measured by a combination of a column (manufactured by Showa Denko K.K., “Shodex (registered trademark) LF-804”) and a differential refractive index detector (manufactured by Showa Denko K.K., “Shodex (registered trademark) RI-71S”).
[0068] In the first step, an organosilicon compound having a structure represented by formula (1) is deposited on the surface of aluminum nitride particles. The deposition can be performed, for example, by a gas phase adsorption method in which the vapor of the organosilicon compound having a structure represented by formula (1) alone or in a mixed gas with an inert gas such as nitrogen is deposited on the surface of the aluminum nitride particles that have been left to stand. Alternatively, the vapor of the organosilicon compound having a structure represented by formula (1) alone or in a mixed gas with an inert gas such as nitrogen can be adsorbed on the surface of the particles while the aluminum nitride particles are stirred.
[0069] The first step is carried out in a nitrogen atmosphere. The partial pressure of the organosilicon compound in the nitrogen atmosphere is 2.6×10 2 ~3.9×10 3 Pa. If the partial pressure of the above organosilicon compound is 2.6×10 2 Pa or more, an appropriate amount of organic silicon compound is deposited on the surface of aluminum nitride particles, which can improve moisture resistance. 3 Pa or less, the rate of change of the particle size distribution width can be reduced, thereby suppressing agglomeration. From this point of view, the partial pressure of the organic silicon compound is preferably 3.2×10 2 ~3.9×10 3 Pa, more preferably 3.9×10 2 ~3.6×10 3 Pa, more preferably 3.9×10 2 ~3.4×10 3 Pa.
[0070] The partial pressure of the organosilicon compound can be within the above range by measuring and controlling the concentration of the organosilicon compound in the reaction container and controlling the amount of the organosilicon compound to be vaporized.
[0071] The treatment temperature is not particularly limited because it depends on the boiling point and vapor pressure of the organosilicon compound having the structure represented by formula (1), but the preferred temperature is 30°C to 200°C, more preferably 40°C to 150°C, and even more preferably 50°C to 100°C.
[0072] The treatment time is not particularly limited, but is preferably 1 to 12 hours, more preferably 2 to 10 hours, and even more preferably 3 to 8 hours.
[0073] Furthermore, if necessary, the system may be pressurized or depressurized. In this case, a closed system is preferred, and a device that can easily replace the gas in the system may be used, such as a glass container, a desiccator, a CVD device, etc.
[0074] The timing of introducing the organosilicon compound having the structure represented by the above formula (1) may be carried out at any stage before the temperature is raised as long as the reaction amount of the organosilicon compound is maintained.
[0075] [Second step]
[0076] In this step, the aluminum nitride particles covered with the organosilicon compound obtained in the first step are heated at a temperature of 300° C. to less than 1000° C., preferably 300° C. to 950° C., more preferably 400° C. to 900° C., and even more preferably 500° C. to 880° C. Thus, an oxide film containing silicon can be formed on the surface of the aluminum nitride particles.
[0077] When the heating in the second step is at a low temperature, a silicon dioxide film is formed on the surface of the aluminum nitride particles, and silicon dioxide-coated aluminum nitride particles can be produced. In addition, when the heating in the second step is at a high temperature, a film of a composite oxide of silicon and aluminum is formed on the surface of the aluminum nitride particles, and aluminum nitride particles coated with a composite oxide of silicon and aluminum can be produced. It is speculated that if the temperature in the second step becomes higher, aluminum constituting the aluminum nitride particles comes out to the surface of the aluminum nitride particles to form a composite oxide together with silicon derived from the organic silicon compound, forming a film of a composite oxide of silicon and aluminum.
[0078] In the second step, as long as the aluminum nitride particles covered with the organosilicon compound obtained in the first step can be heated at a temperature of 300°C to less than 1000°C, preferably 300°C to 950°C, more preferably 400°C to 900°C, and further preferably 500°C to 880°C, that is, as long as the aluminum nitride particles covered with the organosilicon compound obtained in the first step can be maintained in a temperature range of 300°C to less than 1000°C, preferably 300°C to 950°C, more preferably 400°C to 900°C, and further preferably 500°C to 880°C, a general heating furnace can be used.
[0079] It should be noted that the so-called silicon dioxide coating refers to being covered with a thin film with silicon dioxide as the main component. However, since there is a possibility of multiple inorganic composites at the interface between the covered silicon dioxide and the aluminum nitride particles, when analyzed by time-of-flight secondary ion mass spectrometry (ToF-SIMS: Time of Flight Secondary Ion Mass Spectrometry; manufactured by ION-TOF, "TOF.SIMS5"), sometimes the recombination of secondary ions and the decomposition during ionization overlap, and segments such as AlSiO4 ions and SiNO ions are detected as secondary components at the same time. The composite segments analyzed by the ToF-SIMS analysis can also be defined as partial detection objects when aluminum nitride is siliconized. As a standard, as long as the amount of secondary electrons in silicon dioxide is greater than that in other fractions, silicon dioxide can be regarded as the main component.
[0080] As an experiment to further improve the accuracy and confirm the purity of silicon dioxide, the surface of the sample formed with a silicon dioxide film on an aluminum nitride polycrystalline substrate by the same method was measured using a photoelectron spectrometer (XPS: X-ray Photoelectron Spectroscopy; Albuck Fiber, "Quantera II"). The kinetic energy of the photoelectrons detected from Si is almost consistent with the standard peak of silicon dioxide 103.7 eV, so it is speculated that it is basically a SiO2 structure. It should be noted that, depending on the heating temperature, there may also be a situation where organic components remain. As long as it is within the range that does not impair the effect of the present invention, it is possible that the organic siloxane component is mixed.
[0081] The carbon atom content can be measured by a carbon / sulfur analyzer using a non-dispersive infrared absorption method using a tubular electric furnace, etc. Specifically, it can be measured using a carbon / sulfur analyzer (Carbon Anlyzer; manufactured by Horiba, Ltd., "EMIA-821").
[0082] The heating temperature (heat treatment temperature) of the second step is 300°C or more and less than 1000°C, preferably 300°C or more and 950°C or less, more preferably 400°C or more and 900°C or less, and further preferably 500°C or more and 880°C or less. By carrying out the process in this temperature range, an oxide film containing silicon having good moisture resistance and thermal conductivity is formed. Specifically, if the heating is performed at 300°C or more, it may be because the oxide film containing silicon is densified and difficult to penetrate moisture, so the moisture resistance becomes good. In addition, if the heating is performed at less than 1000°C, preferably below 950°C, more preferably below 900°C, and further preferably below 880°C, the thermal conductivity becomes good. On the other hand, if it is above 1000°C, the moisture resistance and thermal conductivity deteriorate. In addition, as long as the heating temperature is 300°C or more and less than 1000°C, preferably 300°C or more and 950°C or less, more preferably 400°C or more and 900°C or less, and further preferably 500°C or more and 880°C or less, an oxide film containing silicon is uniformly formed on the surface of the aluminum nitride particles. In addition, as long as the heating temperature is 300°C or more, the insulating property of the oxide film containing silicon is excellent, and as long as it is less than 1000°C, preferably 950°C or less, more preferably 900°C or less, and further preferably 880°C or less, it is also effective in terms of energy cost. The heating temperature is preferably 500°C or more.
[0083] The heating time is preferably 30 minutes or more and 12 hours or less, more preferably 1 hour or more and 10 hours or less, and even more preferably 2 hours or more and 8 hours or less. When the heat treatment time is 30 minutes or more, no decomposition products of the organic group (alkyl group with 4 or less carbon atoms) of the organosilicon compound remain, and it is preferred to obtain an oxide film containing silicon with a very small carbon atom content on the surface of the aluminum nitride particles. In addition, it is preferred to set the heating time to 12 hours or less in order to produce the oxide-coated aluminum nitride particles containing silicon with good production efficiency.
[0084] The atmosphere of the heat treatment in the second step is not particularly limited, and can be, for example, an atmosphere of an inert gas such as N2, Ar, He, an atmosphere containing a reducing gas such as H2, CO, CH4, or an atmosphere containing oxygen, such as in the atmosphere (air).
[0085] In order to further improve moisture resistance, the first step and the second step may be performed in sequence after the heat treatment in the second step. That is, the first step and the second step may be performed repeatedly.
[0086] In the first step, the coating method of coating the surface of the aluminum nitride particles with an organic silicon compound by a vapor phase adsorption method can form a uniform and thin oxide film containing silicon, compared with the coating method by liquid treatment. Therefore, even if the process of sequentially performing the first step and the second step is repeated multiple times, for example, about 2 to 5 times, the good thermal conductivity of the aluminum nitride particles can be exerted.
[0087] On the other hand, regarding moisture resistance, a positive correlation was confirmed between the number of times the first step and the second step were performed in sequence and moisture resistance. Therefore, the number of times the first step and the second step were performed in sequence can be freely selected according to the level of moisture resistance required in actual use.
[0088] The rate of change of the particle size distribution width (P2) of the silicon-containing oxide-coated aluminum nitride particles obtained by the method for producing silicon-containing oxide-coated aluminum nitride particles of the present invention calculated by the following formula (I) relative to the particle size distribution width (P1) of the aluminum nitride particles is preferably 10% or less, more preferably 8% or less, and even more preferably 7% or less.
[0089]
[0090]
[0091]
[0092] In the formula, D90 in P1 and P2 is the particle size of the particles at 90% of the cumulative volume, D50 is the particle size of the particles at 50% of the cumulative volume, and D10 is the particle size of the particles at 10% of the cumulative volume.
[0093] The rate of change of the particle size distribution width calculated by the above formula (I) is an indicator of the degree of agglomeration of the silicon-containing oxide-coated aluminum nitride particles. The smaller the above rate of change, the more the agglomeration of the silicon-containing oxide-coated aluminum nitride particles is suppressed. If the above rate of change is 10% or less, the agglomeration of the silicon-containing oxide-coated aluminum nitride particles is suppressed, and the filling property into various materials becomes good. In addition, if the agglomeration of the above particles is small, it is not necessary to crush the agglomerated particles when preparing the composition, so the high thermal conductivity of the aluminum nitride particles is maintained, and the silicon-containing oxide-coated aluminum nitride particles have excellent moisture resistance.
[0094] The change rate of the particle size distribution width calculated by the above formula (I) can be within the above range by appropriately adjusting the partial pressure of the organosilicon compound in the nitrogen atmosphere.
[0095] The silicon-containing oxide-coated aluminum nitride particles obtained by the method for producing silicon-containing oxide-coated aluminum nitride particles of the present invention maintain the inherent high thermal conductivity of the aluminum nitride particles and are also excellent in moisture resistance. Therefore, they can be widely used as fillers for heat dissipation materials used in the electrical and electronic fields and the like.
[0096] <Silicon-containing oxide-coated aluminum nitride particles>
[0097] By the method for producing the silicon-containing oxide-coated aluminum nitride particles of the present invention, the silicon-containing oxide-coated aluminum nitride particles of the present invention, that is, the silicon-containing oxide-coated aluminum nitride particles having aluminum nitride particles and a silicon-containing oxide film covering the surface of the aluminum nitride particles, can be obtained. Examples of the "silicon-containing oxide" of the silicon-containing oxide film and the silicon-containing oxide-coated aluminum nitride particles include the above-mentioned silicon dioxide and a composite oxide of silicon element and aluminum element. Examples of the oxide include oxides, oxynitrides, oxycarbonitrides, and the like.
[0098] The silicon-containing oxide-coated aluminum nitride particles of the present invention have a particle size distribution width (P2) calculated by the following formula (I) relative to the particle size distribution width (P1) of the aluminum nitride particles, and the rate of change is preferably 10% or less, more preferably 8% or less, and even more preferably 7% or less.
[0099]
[0100]
[0101]
[0102] In the formula, D90 in P1 and P2 is the particle size of the particles at 90% of the cumulative volume, D50 is the particle size of the particles at 50% of the cumulative volume, and D10 is the particle size of the particles at 10% of the cumulative volume.
[0103] When the change rate is 10% or less, the aggregation of the silicon-containing oxide-coated aluminum nitride particles is suppressed, and the packing property into various materials becomes good. In addition, the silicon-containing oxide-coated aluminum nitride particles have excellent moisture resistance while maintaining the high thermal conductivity of the aluminum nitride particles.
[0104] The silicon-containing oxide-coated aluminum nitride particles of the present invention, for example, when placed in a hydrochloric acid aqueous solution adjusted to pH 4 and treated at 60°C or 85°C for 2 hours (i.e., the silicon-containing oxide-coated aluminum nitride particles are immersed in a hydrochloric acid aqueous solution adjusted to pH 4 at 60°C or 85°C for 2 hours), the concentration of ammonia extracted in the hydrochloric acid aqueous solution can be made to be 10 mg / L or less, and the moisture resistance is extremely excellent. It should be noted that since the hydrolysis reaction is promoted in an acidic solution compared to in the air, an accelerated moisture resistance test can be performed by exposing the particles to a hydrochloric acid aqueous solution adjusted to pH 4. Therefore, by using a hydrochloric acid aqueous solution at pH 4, the moisture resistance of the silicon-containing oxide-coated aluminum nitride particles can be evaluated, and as long as the above-mentioned ammonia concentration is 10 mg / L or less, it can be said that the moisture resistance is good. In addition, by using a hydrochloric acid aqueous solution at pH 4, a comparison of chemical resistance can also be performed.
[0105] The concentration of the extracted ammonia is preferably 8 mg / L or less, more preferably 6 mg / L or less, further preferably 5 mg / L or less, and particularly preferably 4 mg / L or less.
[0106] From the viewpoint of moisture resistance, the lower the content of carbon atoms, the more preferable. Here, in the method for producing the silicon-containing oxide-coated aluminum nitride particles of the present invention, since an organic silicon compound having a structure represented by formula (1) is used as a raw material, the silicon-containing oxide-coated aluminum nitride particles often contain carbon atoms, for example, sometimes contain 50 mass ppm or more, and further 60 mass ppm or more.
[0107] From the viewpoint of achieving a material with better moisture resistance, the content of silicon atoms in the silicon-containing oxide coated on the silicon-containing oxide-coated aluminum nitride particles (ΔSi amount) is preferably 20 to 2000 mass ppm, more preferably 30 to 1900 mass ppm, and further preferably 40 to 1850 mass ppm.
[0108] The ΔSi amount can be measured by an ICP method, and specifically, can be measured by the method described in Examples.
[0109] [Method for producing resin composition]
[0110] The above-mentioned silicon-containing oxide-coated aluminum nitride particles of the present invention can be used to manufacture a resin composition. That is, the method for manufacturing a resin composition in the present invention has the following steps: a manufacturing step of manufacturing silicon-containing oxide-coated aluminum nitride particles by the above-mentioned method for manufacturing silicon-containing oxide-coated aluminum nitride particles; and a mixing step of mixing the silicon-containing oxide-coated aluminum nitride particles with a resin. Examples of the "silicon-containing oxide" of the silicon-containing oxide film and the silicon-containing oxide-coated aluminum nitride particles include the above-mentioned silicon dioxide and a composite oxide of silicon element and aluminum element. As oxides, oxides, oxynitrides, oxycarbonitrides, and the like are included.
[0111] The silicon-containing oxide-coated aluminum nitride particles produced by the method for producing the silicon-containing oxide-coated aluminum nitride particles have good filling properties into the resin composition due to the suppression of aggregation, so the resin composition can be easily produced. In addition, the silicon-containing oxide-coated aluminum nitride particles maintain the high thermal conductivity of the aluminum nitride particles and improve moisture resistance, so the resin composition obtained by the method for producing the resin composition has excellent moisture resistance and thermal conductivity.
[0112] In the mixing step, the silicon-containing oxide-coated aluminum nitride particles produced by the above-mentioned method for producing silicon-containing oxide-coated aluminum nitride particles are mixed with a resin.
[0113] The resin mixed in the mixing process is not particularly limited, but is preferably a thermosetting resin, a thermoplastic resin or a mixture of a thermosetting resin and a thermoplastic resin in terms of the excellent heat resistance of the resin composition obtained. As a thermosetting resin, for example, silicone resins such as polydimethylsiloxane, epoxy resins, phenolic resins, bismaleimide resins, cyanate resins, carbamate resins, (methyl) acrylic resins, vinyl ester resins, unsaturated polyester resins, polyvinyl acetal resins, etc. can be cited, which can be used alone or in combination with two or more. Further, a mixture in which a curing agent and a curing accelerator are added to the thermosetting resin can be used. In particular, epoxy resins are preferred in terms of good heat resistance, adhesion, and electrical properties after curing, and silicone resins are preferred in the purposes of attaching importance to soft adhesion.
[0114] It should be noted that in the silicone resin, there are addition reaction curing type silicone resin, condensation reaction curing type silicone resin, organic peroxide curing type silicone resin, etc., which can be used alone or in combination with two or more different viscosities. In particular, when the obtained resin composition is used in the purpose of attaching importance to soft adhesion, as the silicone resin, for example, an addition reaction curing type liquid silicone resin that does not generate a byproduct of the cause substance of bubbles, etc., can be cited, and the organopolysiloxane with alkenyl as the base polymer and the organopolysiloxane with Si-H group as the crosslinking agent can be reacted at room temperature or heated to obtain the organosilicone resin cured product. It should be noted that as a specific example of the organopolysiloxane as the base polymer, there are, for example, substances with vinyl, allyl, propenyl, hexenyl, etc. as alkenyl. In particular, vinyl is preferred for organopolysiloxane. In addition, the curing catalyst can use, for example, a curing catalyst of a platinum metal system, and in order to achieve the hardness of the resin cured product as the target, the addition amount can also be adjusted and used.
[0115] Examples of the epoxy resin include bifunctional glycidyl ether epoxy resins such as bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol A epoxy resin, and biphenyl epoxy resin; glycidyl ester epoxy resins such as hexahydrophthalic acid glycidyl ester and diol glycidyl ester; linear aliphatic epoxy resins such as epoxidized polybutadiene and epoxidized soybean oil; heterocyclic epoxy resins such as triglycidyl isocyanurate; N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane Glycidylamine type epoxy resins such as oxadiazine, N,N,N',N'-tetraglycidyl-1,3-phenylenedi(methaneamine), 4-(glycidyloxy)-N,N-diglycidylaniline, and 3-(glycidyloxy)-N,N-diglycidylaniline; polyfunctional glycidyl ether type epoxy resins such as phenol novolac type epoxy resins, cresol novolac type epoxy resins, biphenyl aralkyl type epoxy resins, naphthalene aralkyl type epoxy resins, tetrafunctional naphthalene type epoxy resins, and triphenylmethane type epoxy resins; etc. The above epoxy resins may be used alone or in combination of two or more.
[0116] When the epoxy resin is used, a curing agent and a curing accelerator may be mixed. Examples of the curing agent include alicyclic anhydrides such as methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, and nadic anhydride; aliphatic anhydrides such as dodecenylsuccinic anhydride; aromatic anhydrides such as phthalic anhydride and trimellitic anhydride; bisphenols such as bisphenol A, bisphenol F, and bisphenol S; phenolic resins such as phenol / formaldehyde resins, phenol / aralkyl resins, naphthol / aralkyl resins, and phenol-dicyclopentadiene copolymer resins; organic dihydrazides such as dicyandiamide and adipic acid dihydrazide; and the like. Examples of the curing catalyst include amines such as tris(dimethylaminomethyl)phenol, dimethylbenzylamine, 1,8-diazabicyclo(5,4,0)undecene and its derivatives; imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole and its derivatives; and the like. These can be used alone or in combination of two or more.
[0117] In the mixing step, a filler such as boron nitride, aluminum oxide, silicon dioxide, zinc oxide, etc., which is generally used, may be used in combination in addition to the above-mentioned silicon-containing oxide-coated aluminum nitride particles.
[0118] In the mixing step, the silicon-containing oxide-coated aluminum nitride particles and fillers other than the silicon-containing oxide-coated aluminum nitride particles may be mixed in amounts to obtain a desired resin composition.
[0119] The total content of the above-mentioned silicon-containing oxide-coated aluminum nitride particles and fillers other than the above-mentioned silicon-containing oxide-coated aluminum nitride particles in the obtained resin composition is preferably 50% by mass or more and 99% by mass or less, more preferably 60% by mass or more and 97% by mass or less, and further preferably 70% by mass or more and 95% by mass or less. As long as the total content is 50% by mass or more, good heat dissipation can be exerted, and if it is 99% by mass or less, good workability can be obtained when the resin composition is used.
[0120] In addition, the content of the silicon-containing oxide-coated aluminum nitride particles in the obtained resin composition is preferably 30% by mass or more and 100% by mass or less of the total content of the silicon-containing oxide-coated aluminum nitride particles and fillers other than the silicon-containing oxide-coated aluminum nitride particles, more preferably 40% by mass or more and 100% by mass or less, and further preferably 50% by mass or more and 100% by mass or less. When the total content is 30% by mass or more, good heat dissipation can be exhibited.
[0121] In the mixing step, further, flexibility imparting agents such as silicone, urethane acrylate, butyral resin, acrylic rubber, diene rubber and copolymers thereof, silane coupling agents, titanium coupling agents, inorganic ion supplements, pigments, dyes, diluents, solvents, etc. may be appropriately added as needed.
[0122] The mixing method in the mixing step is not particularly limited, and examples thereof include a method in which a dispersing / dissolving device such as a grinding stirrer, a planetary mixer, a rotation / revolution mixer, a kneader, a roll mill, etc. is used alone or in appropriate combination to mix, dissolve, and knead the silicon-containing oxide-coated aluminum nitride particles, a resin, other additives, etc. together or separately, and heat as needed to mix, dissolve, and knead.
[0123] The obtained resin composition can also be formed into a sheet and reacted as needed to form a heat sink. The resin composition and heat sink can be suitably used for bonding semiconductor power devices, power modules, etc.
[0124] As a method for manufacturing a heat sink, there are a method of molding a resin composition by compressing and pressing the resin composition in a form of sandwiching both sides with a base film; a method of coating the resin composition on the base film using a rod coater, screen printing, a doctor blade coater, a die coater, a comma coater, etc. Further, the heat sink after molding / coating may also be subjected to additional treatment steps such as removing the solvent, B-stage treatment by heating, etc., and complete curing. As described above, various forms of heat sinks can be obtained through the process, which can be widely compatible with the intended fields of use and methods of use.
[0125] When the resin composition is coated or formed on the substrate film, a solvent may be used to improve workability. The solvent is not particularly limited, and acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone as ketone solvents may be used alone or in combination of two or more; 1,4-dimethoxybenzene as ether solvents may be used alone or in combination of two or more. alkane, tetrahydrofuran, diethylene glycol dimethyl ether; methyl cellosolve, ethyl cellosolve, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, diethylene glycol methyl ethyl ether as glycol ether solvents; and benzyl alcohol; N-methylpyrrolidone; γ-butyrolactone; ethyl acetate; N,N-dimethylformamide; etc.
[0126] In order to form the resin combination into a sheet, it is necessary to keep the sheet-shaped sheet-forming property. In order to obtain sheet-forming property, a high molecular weight component can be added to the resin combination. For example, phenoxy resin, polyimide resin, polyamide resin, polycarbodiimide resin, cyanate resin, (methyl) acrylic resin, polyester resin, polyethylene resin, polyethersulfone resin, polyetherimide resin, polyvinyl acetal resin, carbamate resin, acrylic rubber, etc. can be cited, wherein, from the viewpoint of excellent heat resistance and film formation, preferably phenoxy resin, polyimide resin, (methyl) acrylic resin, acrylic rubber, cyanate resin, polycarbodiimide resin, etc., more preferably phenoxy resin, polyimide resin, (methyl) acrylic resin, acrylic rubber. They can be used alone or as a mixture or copolymer of two or more.
[0127] The weight average molecular weight of the high molecular weight component is preferably 10,000 or more and 100,000 or less, and more preferably 20,000 or more and 50,000 or less.
[0128] It should be noted that a good sheet shape with good handleability can be maintained by adding a component with a weight average molecular weight within the above range.
[0129] The addition amount of the high molecular weight component is not particularly limited, but in order to maintain the sheet properties, relative to the resin composition, preferably 0.1% by mass or more and 20% by mass or less, more preferably 1% by mass or more and 15% by mass or less, further preferably 2% by mass or more and 10% by mass or less. It should be noted that when the addition amount is 0.1% by mass or more and 20% by mass or less, the operability is also good, and the formation of a good sheet or film can be sought.
[0130] The substrate film used in the manufacture of the heat sink is not particularly limited as long as it can withstand the process conditions such as heating and drying during manufacture, and examples thereof include films formed by polyesters having aromatic rings such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), polypropylene films, polyimide films, polyetherimide films, etc. The above-mentioned film can be a multilayer film composed of two or more kinds of films, or a material whose surface has been treated with a release agent such as a silicone-based film. It should be noted that the thickness of the substrate film is preferably 10 μm or more and 100 μm or less.
[0131] The thickness of the heat sink formed on the base film is preferably 20 μm to 500 μm, more preferably 50 μm to 200 μm. If the thickness of the heat sink is 20 μm or more, a heat sink with a uniform composition can be obtained, and if it is 500 μm or less, good heat dissipation can be obtained.
[0132] Example
[0133] Next, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples in any way.
[0134] <Measurement and calculation methods of physical properties>
[0135] [Cumulative volume 50% particle size (D50)]
[0136] The cumulative volume 50% particle diameter (D50) is determined from the particle diameter at which the cumulative volume becomes 50% in the particle size distribution measured using a laser diffraction / scattering particle size distribution measuring apparatus (manufactured by Microtrac Bell Co., Ltd., “Microtrac MT3300EX2”).
[0137] [Particle size distribution width]
[0138] The cumulative volume 90% particle diameter (D90) and the cumulative volume 10% particle diameter (D10) were determined in the same manner as the measurement of the cumulative volume 50% particle diameter (D50) using a laser diffraction / scattering particle diameter distribution measuring apparatus (manufactured by Microtrac Bell, "Microtrac MT3300EX2"). Using the obtained D10, D50, and D90, the particle size distribution width (P1) of the aluminum nitride particles and the particle size distribution width (P2) of the silicon-containing oxide-coated aluminum nitride particles were calculated by the following formula.
[0139]
[0140]
[0141] [Rate of change in particle size distribution width]
[0142] From P1 and P2 obtained by the above [Particle Size Distribution Width], the change rate of the particle size distribution width (P2) of the silicon-containing oxide-coated aluminum nitride particles relative to the particle size distribution width (P1) of the aluminum nitride particles was calculated by the following formula (I).
[0143]
[0144]
[0145]
[0146] [Evaluation of moisture resistance of particles]
[0147] Regarding the moisture resistance of particles such as silicon-containing oxide-coated aluminum nitride particles, 17 g of a hydrochloric acid aqueous solution adjusted to pH 4 and 3 g of silicon-containing oxide-coated aluminum nitride particles were placed in a 50 mL sample tube and sealed, and then shaken in an oscillating thermostatic bath at 85° C., 80 rpm, and for 2 hours. After standing, the tube was cooled to room temperature (25° C.), and the ammonia concentration in the supernatant was measured at 25° C. using an ammonia electrode (manufactured by Horiba, Ltd., “5002A”). It should be noted that the measurement results are recorded in the “Moisture Resistance Ammonia Concentration” column in the table.
[0148] [Calculation method of silicon atom content (Si content) in silicon-containing oxide-coated aluminum nitride particles]
[0149] The silicon atom content (Si content) of the silicon-containing oxide-coated aluminum nitride particles is calculated by the following procedure.
[0150] (1) Into a 20 mL Teflon (registered trademark) container, 10 mL of a solution prepared by mixing 97 mass % sulfuric acid (ultra-special grade, manufactured by Wako Pure Chemical Industries, Ltd.) and ion-exchanged water at a volume ratio of 1:2 and 0.5 g of a silicon-containing oxide-coated aluminum nitride particle sample were placed.
[0151] (2) The mixture was placed in a stainless steel pressure vessel together with a Tephron (registered trademark) container and maintained at 230° C. for 15 hours to dissolve the silicon-containing oxide-coated aluminum nitride particle sample.
[0152] (3) The solution mixed in (1) was taken out and the concentration of silicon atoms was measured using ICP (manufactured by Shimadzu Corporation, "ICPS-7510"). The silicon atom content (Si amount) of the silicon-containing oxide-coated aluminum nitride particles was calculated from the measured silicon atom concentration (unit: mass ppm).
[0153] [Calculation method of silicon atom content (ΔSi amount) of silicon-containing oxide coated on silicon-containing oxide-coated aluminum nitride particles]
[0154] The content of silicon atoms in the silicon-containing oxide-coated aluminum nitride particles (ΔSi amount) (unit: mass ppm) is calculated by subtracting the silicon content of the aluminum nitride raw material alone calculated by the same method from the content of silicon atoms in the silicon-containing oxide-coated aluminum nitride particles (Si amount) calculated by the above calculation method.
[0155] [Thermal conductivity of resin molded body]
[0156] The thermal conductivity (unit: W / m·K) of the produced resin molded body test pieces and the resin molded body test pieces produced in each of the examples and comparative examples was measured by the following method using a hot plate method using a thermal property measuring apparatus (manufactured by Kyoto Electronics Co., Ltd., “TPS2500S”) in accordance with ISO 22007-2:2015.
[0157] (Manufacture of resin molded body)
[0158] Polydimethylsiloxane gel (manufactured by Dow Toray Co., Ltd., "DOWSIL TM Liquid A and liquid B of EG-3100" were weighed into a container at 50% by mass relative to a total of 100 parts by mass, and various fillers were weighed in such a manner as to obtain the composition (parts by mass) described in Table 1. The mixture was stirred and mixed while reducing the pressure at a rotation speed of 1000 rpm for 30 seconds using a rotation / revolution mixer (manufactured by Shinki Co., Ltd., "ARV-310P"). The mixture was temporarily cooled to room temperature (25°C). Compositions 1 to 6 were placed on a PET substrate, sandwiched between the PET substrates, stretched to a thickness of 2 mm using a roller, and then cured by heat treatment at 100°C for 15 minutes to obtain resin molded body test pieces 1 to 6.
[0159] Herein, the details of each component in Table 1 are shown below.
[0160] Aluminum nitride particles A: "N01P" manufactured by Toyo Aluminum Co., Ltd.; D50 = 1.3 μm
[0161] Aluminum nitride particles B: manufactured by Toyo Aluminum Co., Ltd., “JM”; D50 = 2.8 μm
[0162] Aluminum nitride particles C: manufactured by Toyo Aluminum Co., Ltd., “TFZ-N15P”; D50 = 17.0 μm
[0163] Aluminum nitride particles D: "FAN-f30-A1" manufactured by Furukawa Electronics Co., Ltd.; D50 = 32.8 μm
[0164] Aluminum nitride particles E: manufactured by Furukawa Electronics Co., Ltd., “FAN-f50-A1”; D50 = 45.5 μm
[0165] Aluminum nitride particles F: manufactured by Furukawa Electronics Co., Ltd., “FAN-f80-A1”; D50 = 77.6 μm
[0166] AA-3: Advanced alumina (manufactured by Sumitomo Chemical Co., Ltd., "SUMICOMDAMU (registered trademark)"; D50 = 3 μm)
[0167] AKP-30: high-purity alumina (manufactured by Sumitomo Chemical Co., Ltd., “AKP-30”; D50 = 0.3 μm)
[0168] EG-3100(A): dimethicone gel (manufactured by Dow Toray Co., Ltd., "DOWSIL TM Liquid A of EG-3100 (mixture of vinyl oil and platinum catalyst, viscosity 420 mPa·s)
[0169] EG-3100(B): dimethicone gel (manufactured by Dow Toray Co., Ltd., "DOWSIL TM EG-3100”) Liquid B (mixture of vinyl oil and crosslinking agent, viscosity 320mPa·s)
[0170] [Table 1]
[0171] Table 1
[0172] Unit: mass parts Composition 1 Composition 2 Composition 3 Composition 4 Composition 5 Composition 6 Aluminum Nitride Particles A 400 ― ― ― ― ― Aluminum Nitride Particles B ― 400 ― ― ― ― Aluminum Nitride Particles C ― ― 800 ― ― ― Aluminum Nitride Particles D ― ― ― 800 ― ― Aluminum Nitride Particles E ― ― ― ― 800 ― Aluminum Nitride Particles F ― ― ― ― ― 800 AA-3 ― ― 300 300 300 300 AKP-30 160 160 400 400 400 400 EG-3100(A) 50 50 50 50 50 50 EG-3100(B) 50 50 50 50 50 50
[0173] (Example 1)
[0174] [Production of Silica-Coated Aluminum Nitride Particles]
[0175] In the first step, a reaction device based on a large oven with a reaction tank internal volume of 250L was used to coat the surface of aluminum nitride particles. In the reaction tank, 50g of aluminum nitride particles A, aluminum nitride particles B, aluminum nitride particles C, aluminum nitride particles D, aluminum nitride particles E, and aluminum nitride particles F were evenly spread on another stainless steel tray and left to stand. Next, 84g of an organosilicon compound A (cyclic methyl hydrogen siloxane tetramer; manufactured by Tokyo Chemical Industry Co., Ltd., "D4H") with n=4 in formula (3) was added to 4 glass dishes (inner diameter 150mm×height 20mm) in the reaction tank, with 21g in each glass dish, and left to stand, and the reaction tank was closed. Since hydrogen gas is generated by the reaction, the reaction tank was evacuated in advance until the oxygen concentration became less than 8% by volume, which is the explosion limit, and then dry nitrogen gas was flowed into the reaction tank to restore the internal pressure to normal pressure (0.1MPa). Then, the reaction tank was heated to 80° C. to vaporize the organosilicon compound A, and the reaction was carried out for 7.5 hours after the temperature stabilized. It should be noted that the partial pressure of the organosilicon compound A in the nitrogen atmosphere inside the reaction tank at the start of the first step was 3.3×10 3 Pa.
[0176] After completing the first step, samples A to F taken out from the reaction tank were respectively added to alumina crucibles, and subjected to the second step of heat treatment in the atmosphere at 700°C for 3 hours for samples A to C and at 850°C for 6 hours for samples D to F, thereby obtaining silicon dioxide-coated aluminum nitride particles 1-A to 1-F, which are silicon-containing oxide-coated aluminum nitride particles.
[0177] In addition, in the above (Manufacture of resin molded body), the aluminum nitride particles A to F in Table 1 were respectively changed to silica-coated aluminum nitride particles 1-A to 1-F. Except for this, the same operation as the above (Manufacture of resin molded body) was carried out to prepare compositions 1-A to 1-F, and further obtain resin molded body test pieces 1-A to 1-F.
[0178] (Example 2)
[0179] In Example 1, the partial pressure of the organosilicon compound A in the nitrogen atmosphere in the first step was changed from 3.3×10 3 Pa was changed to 1.6×10 3 Pa, except for this, the same operation as in Example 1 was carried out to obtain silica-coated aluminum nitride particles 2-A to 2-F. In addition, in the above (Manufacture of resin molded body), the aluminum nitride particles A to F in Table 1 were respectively changed to silica-coated aluminum nitride particles 2-A to 2-F, and the same operation as in the above (Manufacture of resin molded body) was carried out to prepare compositions 2-A to 2-F, and further obtain resin molded body test pieces 2-A to 2-F.
[0180] (Example 3)
[0181] In Example 1, the partial pressure of the organosilicon compound A in the nitrogen atmosphere in the first step was changed from 3.3×10 3 Pa was changed to 8.1×10 2 Pa, except for this, the same operation as in Example 1 was carried out to obtain silica-coated aluminum nitride particles 3-A to 3-F. In addition, in the above (Manufacture of resin molded body), the aluminum nitride particles A to F in Table 1 were respectively changed to silica-coated aluminum nitride particles 3-A to 3-F, and the same operation as in the above (Manufacture of resin molded body) was carried out to prepare compositions 3-A to 3-F, and further obtain resin molded body test pieces 3-A to 3-F.
[0182] (Example 4)
[0183] In Example 1, the partial pressure of the organosilicon compound A in the nitrogen atmosphere in the first step was changed from 3.3×10 3 Pa was changed to 4.1×10 2Pa, except for this, the same operation as in Example 1 was carried out to obtain silica-coated aluminum nitride particles 4-A to 4-F. In addition, in the above (Manufacture of resin molded body), the aluminum nitride particles A to F in Table 1 were respectively changed to silica-coated aluminum nitride particles 4-A to 4-F, and the same operation as in the above (Manufacture of resin molded body) was carried out to prepare compositions 4-A to 4-F, and further obtain resin molded body test pieces 4-A to 4-F.
[0184] (Comparative Example 1)
[0185] In Example 1, the partial pressure of the organosilicon compound A in the nitrogen atmosphere in the first step was changed from 3.3×10 3 Pa was changed to 1.32×10 4 Pa, except for this, the same operation as in Example 1 was carried out to obtain silica-coated aluminum nitride particles 5-A to 5-F. In addition, in the above (Manufacture of resin molded body), the aluminum nitride particles A to F in Table 1 were respectively changed to silica-coated aluminum nitride particles 5-A to 5-F, and the same operation as in the above (Manufacture of resin molded body) was carried out to prepare compositions 5-A to 5-F, and further obtain resin molded body test pieces 5-A to 5-F.
[0186] In addition, the obtained silica-coated aluminum nitride particles 5-A and 5-B were stirred and mixed while being depressurized at a rotation speed of 2000 rpm for 30 seconds using a rotation / revolution mixer (manufactured by Shinki Co., Ltd., "ARV-310P"). They were temporarily cooled to room temperature (25°C). This was repeated multiple times, and after appropriately sampling and confirming the particle size distribution, mechanochemical pulverization was repeated until the change rate of the particle size distribution width became less than 10%, thereby obtaining silica-coated aluminum nitride particles 5-A1 and 5-B1.
[0187] (Comparative Example 2)
[0188] In Example 1, the partial pressure of the organosilicon compound A in the nitrogen atmosphere in the first step was changed from 3.3×10 3 Pa was changed to 2.06×10 2 Pa, except for this, the same operation as in Example 1 was carried out to obtain silica-coated aluminum nitride particles 6-A to 6-F. In addition, in the above (Manufacture of resin molded body), the aluminum nitride particles A to F in Table 1 were respectively changed to silica-coated aluminum nitride particles 6-A to 6-F, and the same operation as in the above (Manufacture of resin molded body) was carried out to prepare compositions 6-A to 6-F, and further obtain resin molded body test pieces 6-A to 6-F.
[0189] [Table 2]
[0190] Table 2:
[0191]
[0192] [Table 3]
[0193]
[0194] [Table 4]
[0195]
[0196] It can be seen that in Examples 1 to 4, in the first step of the method for producing silicon-containing oxide-coated aluminum nitride particles, by setting the partial pressure of the organic silicon compound in the nitrogen atmosphere to be within the range specified in claim 1, the change rate of the particle size distribution width can be made 10% or less, and silicon-containing oxide-coated aluminum nitride particles with suppressed aggregation can be obtained. In addition, the silicon-containing oxide-coated aluminum nitride particles of Examples 1 to 4 have high thermal conductivity and excellent moisture resistance.
[0197] On the other hand, the partial pressure of the organosilicon compound in a nitrogen atmosphere is 1.32×10 4 In Comparative Example 1 where Pa is greater than the above range, the change rate of the particle size distribution width is greater than 10%, and it can be said that the obtained silicon-containing oxide-coated aluminum nitride particles are agglomerated. In addition, if the particles are crushed, the change rate of the particle size distribution width is reduced, but the moisture resistance is reduced (refer to 5-A1 and 5-B1). In addition, in the first step, the partial pressure of the organic silicon compound in the nitrogen atmosphere is 2.06×10 2 In Comparative Example 2 where Pa was smaller than the above range, the moisture resistance was low.
Claims
1. A method for producing silicon-containing oxide-coated aluminum nitride particles, the silicon-containing oxide-coated aluminum nitride particles comprising aluminum nitride particles and a silicon-containing oxide film covering the surface of the aluminum nitride particles, the method comprising the following steps: A first step of vapor-depositing an organosilicon compound including a compound represented by the following formula (3) on the surface of the aluminum nitride particles to obtain the aluminum nitride particles covered with the organosilicon compound; and a second step of heating the aluminum nitride particles covered with the organic silicon compound at a temperature of 300° C. or more and less than 1000° C., The first step is performed in a nitrogen atmosphere, and the partial pressure of the organosilicon compound in the nitrogen atmosphere is 2.6×10 2 ~3.9×10 3 Pa, The change rate of the particle size distribution width P2 of the silicon-containing oxide-coated aluminum nitride particles with respect to the particle size distribution width P1 of the aluminum nitride particles calculated by the following formula (I) is 10% or less, In formula (3), n is an integer from 3 to 6, Particle size distribution width Particle size distribution width In the formula, D90 in P1 and P2 is the particle size of the particles at 90% of the cumulative volume, D50 is the particle size of the particles at 50% of the cumulative volume, and D10 is the particle size of the particles at 10% of the cumulative volume. 2 . The method for producing silicon-containing oxide-coated aluminum nitride particles according to claim 1 , wherein the first step is performed by a vapor phase adsorption method. 3 . The method for producing silicon-containing oxide-coated aluminum nitride particles according to claim 1 , wherein the first step is performed under a temperature condition of 30 to 200° C.
Citation Information
Patent Citations
Method for producing silicon-containing oxide-coated aluminum nitride particles and method for producing heat dissipation resin composition
JP2021075435A
Method for producing silicon-containing oxide-coated aluminum nitride particles, and silicon-containing oxide-coated aluminum nitride particles
WO2020040309A1
Method for producing silicon-containing oxide-coated aluminum nitride particles, and silicon-containing oxide-coated aluminum nitride particles
CN112585087A